Morphological assessment to predict genetic variability for leaf yield and component traits in Moringa (Moringa oleifera) - MANDAL, SUPRIYA; SHANKAR, RAJA; HANCHINAMANI, C N; ANJANAPPA, M; KUMAR J S, ARVIND (The Indian Journal of Agricultural Sciences, 2022)
Moringa (Moringa oleifera L.) is primarily grown for its pod but nowadays it is gaining demands for leaf production. Moringa leaves have immense medicinal and dietary value to supplement nutrients for good health. Therefore, identification and selection of leafy type genotype(s) is imperative. Fifty-two genotypes collected from diversified areas of India were evaluated at Division of Vegetable crops, ICAR-IIHR, Bengaluru from 2018–2020. Analysis of variance for growth and leaf yield traits indicated existence of considerable genetic variability in the gene pool. Magnitude of phenotypic coefficient of variation was higher than its genotypic level for all the traits, indicating the environmental influence on their expression. Higher genotypic and phenotypic coefficient of variation was observed for all the leaf yield traits indicating that higher variability and simple selection would be effective. High heritability was recorded for all growth and leaf yield related traits (60.74–99.89%) except number of primary rachis per leaf (35.66%), suggesting selection based on phenotypic expression is effective for improvement. The estimate of genetic advance as per cent mean value was high for all growth and leaf yield related traits except edible leaf per cent and number of primary rachis per leaf, revealing that additive gene action and selection approach is most helpful for improvement of these characters. High heritability coupled with high genetic advance was observed for stem length, whole leaf weight/shoot and edible leaf weight/shoot which revealed that these characters are under additive gene action and showed higher responses of these trait towards selection.